Innovation failure and learning from innovation failure in micro, small and medium enterprises (MSMEs): a qualitative approach: english - Putri, Esty Prema; Games, Donard; Sari, Dessy Kurnia (Enrichment : Journal of Management, 2023)
Innovation is one of the most important activities today. Because innovation is often a guarantee for business people to achieve market advantage. Unfortunately, not everyone can innovate well. Even though we implement innovation steps related to the search for new solutions, new products or new technology by investing, we can fail or succeed. This type of research is qualitative using semi-structured interview data collection techniques. The number of MSMEs data studied was 20 MSMEs. The research results show that innovation failure can be caused by several things, lack of innovative ideas, rigid local government regulations, lack of market share, undisciplined workforce, employee behavioral culture, poor product quality, unstrategic location, personality that is not easily influenced, missed customers. Lessons learned from innovation failure can be obtained from family motivation, self-motivation, curiosity, openness to the knowledge among employees, product consistency, modern machine tools, and improving service to consumers. The conclusion of this research is that each type MSMEs has very diverse innovation failures and learning from innovation failures in each MSMEs is also different. In previous research, it only discussed innovation failure, whereas in this research, innovation failure and learning from innovation failure are discussed.